Functional analysis of centipede development supports roles for Wnt genes in posterior development and segment generation. Issue 1 (January 2015) - Hayden, Luke; Schlosser, Gerhard; Arthur, Wallace
SUMMARY The genes of the Wnt family play important and highly conserved roles in posterior growth and development in a wide range of animal taxa. Wnt genes also operate in arthropod segmentation, and there has been much recent debate regarding the relationship between arthropod and vertebrate segmentation mechanisms. Due to its phylogenetic position, body form, and possession of many (11) Wnt genes, the centipede Strigamia maritima is a useful system with which to examine these issues. This study takes a functional approach based on treatment with lithium chloride, which causes ubiquitous activation of canonical Wnt signalling. This is the first functional developmental study performed in any of the 15, 000 species of the arthropod subphylum Myriapoda. The expression of all 11 Wnt genes in Strigamia was analyzed in relation to posterior development. Three of these genes, Wnt11, Wnt5, and WntA, were strongly expressed in the posterior region and, thus, may play important roles in posterior developmental processes. In support of this hypothesis, LiCl treatment of S. maritima embryos was observed to produce posterior developmental defects and perturbations in AbdB and Delta expression. The effects of LiCl differ depending on the developmental stage treated, with more severe effects elicited by treatment during germband formation than by treatment at later stages. These results support a role for Wnt signalling in conferring posterior identity in Strigamia. In addition, data from this study are consistent with the hypothesis of segmentation based on a "clock and wavefront" mechanism operating in this species.